A numerical simulation of tube geometry effect on the performance of regenerators in Organic Rankine Cycle systems using the Volume of Fluid method. (5th November 2022) - Lin, Yu-Chen; Lin, Chia-Wei; Kumar, Ranjith; Lin, Kai-Qi; Hsu, Hua-Yi; Hung, Tzu-Chen
Highlights: The geometry effect on heat flux/pressure drop in boiling has been studied by VOF. Divergent tube is 34.5% lower pressure drop and 2.94% higher heat flux than normal. Divergent tube enhances heat transfer and reduces pressure drop with fluctuation. Divergent tube can be as a novel design for the liquid side of regenerators in ORC. Convergent tube induces higher pressure drop/higher heat flux before bubble clogging. Abstract: In this work, the tube geometry effect on the performance of regenerators in ORC systems is numerically studied using the Volume of Fluid (VOF) method. Three tube geometries are investigated: normal, divergent, and convergent tubes. The divergent tube offers increasing space, which is beneficial to bubble growth and delay the tube clogging induced by the increasing bubble size. The delay of tube clogging in the divergent tube can benefit the boiling heat transfer performance. The decreasing flow velocity due to the increasing space can also reduce the friction pressure drop. As a result, the divergent tube induces smaller total pressure drop as well as less pressure fluctuation, which are good for pump efficiency. It is found that the pressure drop can be up to 34.5% lower in divergent tube while the averaged wall heat flux is 2.94% higher comparing with the normal one. The features of enhancing heat transfer performance and reducing total pressure drop with less pressure fluctuation of the divergent tube can be used as a novel design for the liquid side of regenerators. The convergent tube will induce higher pressure drop with higher heat flux before the tube is clogged by the bubbles. However, the heat flux decreases as the tube clogging occurs. Due to the higher pressure drop induced, the convergent tube might not be suitable for the design of the liquid side of regenerators. It is the first time to study the heat transfer problem with a single vapor bubble considering the geometric effect, and this work provides physical insights on heat transfer performance and pressure drop for a two-phase boiling flow. The optimized geometry can increase the energy efficiency, whch could profoundly impact many industrial applications.